The politics of digital sovereignty and the European Union’s legislation: navigating crises - Gábor Hulkó; János Kálmán; András Lapsánszky (Frontiers in Political Science)
In recent years, the resistance of member states to the strengthening of the European Union and its ambition to extend the powers of nation states has become a dominant political element, especially in the countries of the Central and Eastern European region. At the same time, both nation states and the EU are facing a number of global challenges, one of the most significant of which, alongside climate change, is digitalization. At the dawn of the digital age, technological innovation and the free flow of information promised unprecedented opportunities. However, as digital technologies have increasingly permeated all aspects of economic, social and political life, they have created new crises and challenges, particularly with regard to digital sovereignty. This research explores the complex and interdisciplinary nature of digital sovereignty, with a particular focus on the crises that digitalization has triggered and caused. These crises manifest themselves in various forms, including cybersecurity threats, privacy issues and the economic dominance of global technology companies. The European Union’s legislative initiatives, including the Digital Services (DSA), Digital Markets (DMA) and European Media Freedom (EMFA) regulations, as well as the efforts to regulate artificial intelligence, are designed to address the crises inherent in the digital age, while at the same time posing new challenges to the sovereignty and perception of sovereignty of individual states. The research examines the EU’s legislative efforts in navigating the politics of digital crises. It sheds light on the interplay between national self-determination and the EU’s overall regulatory framework, highlighting the ongoing struggle to balance control and cooperation in a rapidly changing digital environment. The analysis will provide a deeper understanding of how digital sovereignty is shaped by and responds to crisis policy, and insights into the future of digital governance in an increasingly interconnected world. It also seeks to assess the extent to which recently introduced EU legislation can be harmonized with the policy objective of strengthening the autonomy of nation states. This is particularly important in the context of the legislation and practices observed in countries with relatively small populations, such as Hungary, Slovakia and the Czech Republic.